2019
DOI: 10.1111/jam.14230
|View full text |Cite
|
Sign up to set email alerts
|

Hsp BP 1 and anti‐Hsp BP 1 levels in the serum of HIV ‐infected individuals are associated to the disease progression

Abstract: Aims The objective of this research was to quantify the levels of circulating HspBP1 and anti‐HspBP1 IgG in HIV‐infected individuals and to correlate them with CD4 T cell counts and viral load, as well as to determine the kinetics of those proteins during acute phase. Methods and Results Sixty serum samples from HIV‐positive outpatients, thirty with high viral load and thirty with low viral load were analysed. The HspBP1 and anti‐HspBP1 were quantified by ELISA. To investigate the kinetic of HspBP1 and anti‐Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…HspBP1 and anti-HspBP1 negatively correlated with CD4 counts. In the acute phase, HspBP1 was significantly increased 15 days after HIV infection [35]. Our previous study showed that overexpression of Hsp27, similar to Hsp20, significantly decreased herpes simplex virus-1 (HSV-1) replication, but it did not affect the replication of human immunodeficiency virus-1 (HIV-1) and hepatitis C virus (HCV) in vitro.…”
Section: Figmentioning
confidence: 99%
“…HspBP1 and anti-HspBP1 negatively correlated with CD4 counts. In the acute phase, HspBP1 was significantly increased 15 days after HIV infection [35]. Our previous study showed that overexpression of Hsp27, similar to Hsp20, significantly decreased herpes simplex virus-1 (HSV-1) replication, but it did not affect the replication of human immunodeficiency virus-1 (HIV-1) and hepatitis C virus (HCV) in vitro.…”
Section: Figmentioning
confidence: 99%